Composite material for activating persulfate as well as preparation method and application of composite material

The heterojunction is constructed through the composite of V2O5 and g-C3N4, which solves the problem that catalytic materials cannot activate persulfate under light conditions, and achieves efficient catalytic activity without additional energy input, and has extensive application prospects for water pollution control.

CN119869583APending Publication Date: 2025-04-25GUANGDONG UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411950632.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

Existing catalytic materials cannot effectively activate persulfate without additional energy input, limiting their application of water pollution control in light-free scenarios.

Method used

By compounding V2O5 with g-C3N4, a V2O5/g-C3N4 heterojunction with strong interaction is constructed, forming a built-in electric field, reducing the band gap, enhancing electron transfer, and accelerating the conversion of vanadium valence state, thereby promoting the activation of persulfate.

Benefits of technology

In the absence of additional energy input, the V2O5/g-C3N4 composite material can effectively activate persulfate, significantly improving its catalytic activity under light-free conditions, and has wide application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869583A_ABST
    Figure CN119869583A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of water environment treatment, in particular to a composite material for activating persulfate as well as a preparation method and application of the composite material. Wherein the composite material for activating the persulfate comprises V2O5 and g-C3N4, and the composite material is used for activating the persulfate under the condition of no extra energy input. V2O5 and g-C3N4 are compounded to construct a V2O5 / g-C3N4 heterojunction with strong interaction, and the heterojunction forms a built-in electric field, reduces a band gap, enhances transfer of electrons from g-C3N4 to V2O5 and accelerates conversion of vanadium valence states, so that activation of persulfate is remarkably promoted, and persulfate can be effectively activated under the condition of no extra energy input.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of water environment treatment, and in particular to an activated persulfate composite material and a preparation method and application thereof. Background Art

[0002] Chloramphenicol (CAP) is a highly effective and broad-spectrum antibiotic widely used in medicine, agriculture, aquaculture and other fields. Due to its aromatic nitro structure, it is difficult to remove by traditional biochemical and oxidation technologies, resulting in its frequent detection in various water sources such as groundwater, surface water and wastewater. Due to its serious toxic side effects, long-term trace intake of chloramphenicol will not only lead to irreversible bone marrow function suppression in humans, causing aplastic anemia and cardiovascular failure, but also cause bacteria to develop CAP resistance and the normal flora of the human body to be imbalanced, with reduced resistance and susceptibility to various diseases. Therefore, residual CAP in water poses a major threat to the environment and human health, and there is an urgent need to develop new technologies for decontamination.

[0003] Graphitic carbon nitride (g-C3N4) and V2O5 can both activate persulfate through photocatalysis under illumination conditions, but under conditions where no additional energy is input, for example: under lightless conditions, graphitic carbon nitride and V2O5 cannot effectively activate persulfate. Therefore, based on the photocatalytic properties of g-C3N4 and V2O5, their water pollution control technology under lightless conditions is subject to certain limitations (such as groundwater remediation). Based on this, there is an urgent need for a catalytic material that can effectively activate persulfate without inputting additional energy to solve the problem of limited application of current catalytic materials in lightless scenarios such as groundwater pollution. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is to overcome the problem that existing catalytic materials such as g-C3N4 and V2O5 are limited in the activation reaction of persulfate without additional energy input, thereby providing a composite material for activating persulfate and its preparation method and application to solve the above problem.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] In a first aspect, the present invention provides a composite material for activating persulfate, wherein the composite material comprises V2O5 and g-C3N4, and the composite material activates persulfate without additional energy input.

[0007] In a second aspect, the present invention also provides a method for preparing the above-mentioned activated persulfate composite material, comprising: obtaining g-C3N4; mixing g-C3N4 and NH4VO3 to obtain a mixed material; and calcining the mixed material.

[0008] Preferably, the mass ratio of g-C3N4 to NH4VO3 is 2:(0.2-1.4);

[0009] And / or, the calcination temperature is 400-600°C, preferably 500°C;

[0010] And / or, the calcination treatment time is 1-3 hours, preferably 2 hours;

[0011] And / or, the heating rate of the calcination treatment is 1-5°C / min, preferably 2.5°C / min;

[0012] And / or, the specific process of the mixing treatment includes: dispersing g-C3N4 and NH4VO3 in a solvent to obtain a dispersion, and stirring the dispersion in a water bath until the solvent is completely evaporated;

[0013] And / or, the calcination treatment is followed by natural cooling and grinding.

[0014] Preferably, the solvent is water;

[0015] And / or, based on the mass of g-C3N4 being 2g, the amount of the solvent used is 40-60mL, preferably 50mL;

[0016] And / or, the temperature of the water bath is 65-85°C, preferably 75°C.

[0017] Preferably, the method for obtaining the g-C3N4 comprises: sintering melamine.

[0018] Preferably, the sintering temperature is 500-600°C, preferably 550°C;

[0019] And / or, the sintering treatment time is 3-5 hours, preferably 4 hours;

[0020] And / or, the heating rate of the sintering treatment is 4-6°C / min, preferably 5°C / min;

[0021] And / or, the sintering process is followed by natural cooling and grinding.

[0022] In a third aspect, the present invention also provides the use of the above-mentioned activated persulfate composite material or the activated persulfate composite material prepared by the above-mentioned method for preparing the activated persulfate composite material in activating persulfate without additional energy input.

[0023] Preferably, the composite material degrades pollutants in water by activating persulfate.

[0024] Preferably, the persulfate is peroxymonosulfate or / and peroxydisulfate, preferably peroxymonosulfate;

[0025] And / or, the pollutant is an organic pollutant.

[0026] Preferably, the organic pollutants include bisphenol S (BPS), chloramphenicol (CAP), atrazine (ATZ), bisphenol F (BPF), sulfamethoxazole (SMX), 4-Cl-phenol (4-CP), caffeine (CAF), and bisphenol A (BPA).

[0027] In the present invention, the atmosphere of the calcination treatment may be an open gas (air) or an inert atmosphere (nitrogen, etc.), that is, there is no requirement for the calcination atmosphere.

[0028] In the present invention, the condition without additional energy input is a condition without light.

[0029] The technical solution of the present invention has the following advantages:

[0030] A composite material for activating persulfate, the composite material includes V2O5 and g-C3N4, and the composite material activates persulfate without additional energy input. The present invention constructs a V2O5 / g-C3N4 (V-CN) heterojunction with strong interaction by compounding V2O5 with g-C3N4, the heterojunction forms a built-in electric field, reduces the band gap, enhances the transfer of electrons from g-C3N4 to V2O5, accelerates the conversion of vanadium valence states, thereby significantly promoting the activation of persulfate, and can effectively activate persulfate without additional energy input. In addition, the V2O5 / g-C3N4 / persulfate system exhibits a wide operating pH range (pH=2-10), a strong ability to resist matrix interference, and excellent persistence and stability, and has broad application prospects in persulfate activation (for example, in achieving degradation of new pollutants in actual water bodies through persulfate activation). BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 It is the XRD (X-ray diffraction) diagram of the V2O5 / g-C3N4 composite materials prepared in Examples 1-4 of the present invention, the g-C3N4 prepared in Comparative Example 1, and the V2O5 prepared in Comparative Example 2;

[0033] Figure 2 It is the full spectrum of XPS (X-ray photoelectron spectroscopy) of V-CN-3 prepared in Example 3 of the present invention and g-C3N4 prepared in Comparative Example 1;

[0034] Figure 3 FT-IR (Fourier transform infrared spectrum) diagram of V-CN-3 prepared in Example 3 of the present invention, g-C3N4 prepared in Comparative Example 1, and V2O5 prepared in Comparative Example 2;

[0035] Figure 4 FT-IR graph of the V2O5 / g-C3N4 composite material prepared in Examples 1-4 of the present invention;

[0036] Figure 5 This is a SEM (scanning electron microscope) image of g-C3N4 prepared in Comparative Example 1 of the present invention at a scale length of 1 μm;

[0037] Figure 6 This is a SEM (scanning electron microscope) image of g-C3N4 prepared in Comparative Example 1 of the present invention at a scale length of 200 μm;

[0038] Figure 7 is a SEM (scanning electron microscope) image of V-CN-3 prepared in Example 3 of the present invention at a scale length of 1 μm;

[0039] Figure 8 is a SEM (scanning electron microscope) image of V-CN-3 prepared in Example 3 of the present invention at a scale length of 200 μm;

[0040] Fig. 9 This is a SEM (scanning electron microscope) image of V2O5 obtained in Comparative Example 2 of the present invention at a scale length of 1 μm;

[0041] Fig.10 This is a SEM (scanning electron microscope) image of V2O5 prepared in Comparative Example 2 of the present invention at a scale length of 200 μm;

[0042] Fig.11 is the adsorption-desorption equilibrium diagram of CAP by different catalytic materials;

[0043] Fig.12 It is a graph of CAP degradation efficiency in different reaction systems (using PMS (permonosulfate) alone or using different catalytic materials combined with PMS);

[0044] Fig.13 It is a comparison chart of the reaction rate constants of the V2O5 / g-C3N4 composite materials prepared in Examples 1-4, the g-C3N4 prepared in Comparative Example 1, and the V2O5 activated PMS prepared in Comparative Example 2;

[0045] Fig.14 This is a comparison chart of the apparent first-order degradation kinetic rate constants of CAP by V-CN-3 prepared in Example 3 of the present invention and the existing catalytic system;

[0046] Fig.15 is a V 2p XPS high-resolution spectrum of V-CN-3 prepared in Example 3 of the present invention before and after the PMS activation reaction;

[0047] Fig.16 This is the effect of different V-CN-3 dosages on the CAP degradation effect of the V-CN-3 / PMS system;

[0048] Fig.17 This is the effect of different PMS concentrations on the degradation of CAP by the V-CN-3 / PMS system;

[0049] Fig.18 This is the effect of different CAP concentrations on the CAP degradation effect of the V-CN-3 / PMS system;

[0050] Fig.19 This is the effect of different pH values ​​on the degradation of CAP by V-CN-3 / PMS system;

[0051] Fig. 20 This is the effect of different ions and humic acid (HA) on the degradation of CAP by V-CN-3 / PMS system;

[0052] Fig.21 It is the effect of different water bodies on the degradation of CAP by V-CN-3 / PMS system;

[0053] Fig. 22 This is the V-CN-3 cycle stability test graph;

[0054] Fig.23 It is the degradation effect of V-CN-3 / PMS system on different pollutants. DETAILED DESCRIPTION

[0055] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0056] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0057] Example 1

[0058] This embodiment provides a method for preparing a V2O5 / g-C3N4 composite material, and the specific steps are as follows:

[0059] 1) 5 g of melamine was placed in a covered crucible, and then placed in a muffle furnace, and calcined at 550 ° C for 4 h in an air atmosphere, with a heating rate of 5 ° C / min. After the crucible was naturally cooled to room temperature, the collected solid was ground into powder, which was marked as g-C3N4;

[0060] 2) dispersing the g-C3N4 (2 g) and NH4VO3 (0.2 g) obtained in step 1) in 50 mL of ultrapure water, and stirring in a water bath at 75° C. until the water is completely evaporated to obtain a mixed material;

[0061] 3) The mixture obtained in step 2) was encapsulated in a crucible and wrapped tightly with tin foil, and calcined at 500°C for 2h in an air atmosphere with a heating rate set at 2.5°C / min. After the crucible was naturally cooled to room temperature, the collected solid was ground evenly and marked as V-CN-1.

[0062] Example 2

[0063] This embodiment provides a method for preparing a V2O5 / g-C3N4 composite material, and the specific steps are as follows:

[0064] 1) 5 g of melamine was placed in a covered crucible, and then placed in a muffle furnace, and calcined at 550 ° C for 4 h in an air atmosphere, with a heating rate of 5 ° C / min. After the crucible was naturally cooled to room temperature, the collected solid was ground into powder, which was marked as g-C3N4;

[0065] 2) dispersing the g-C3N4 (2 g) and NH4VO3 (0.6 g) obtained in step 1) in 50 mL of ultrapure water, and stirring in a water bath at 75° C. until the water is completely evaporated, to obtain a mixed material;

[0066] 3) The mixture obtained in step 2) is encapsulated in a crucible and wrapped with tin foil, and calcined at 500°C for 2h in an air atmosphere with a heating rate of 2.5°C / min. After the crucible is naturally cooled to room temperature, the collected solid is ground evenly and marked as V-CN-2.

[0067] Example 3

[0068] This embodiment provides a method for preparing a V2O5 / g-C3N4 composite material, and the specific steps are as follows:

[0069] 1) 5 g of melamine was placed in a covered crucible, and then placed in a muffle furnace, and calcined at 550 ° C for 4 h in an air atmosphere, with a heating rate of 5 ° C / min. After the crucible was naturally cooled to room temperature, the collected solid was ground into powder, which was marked as g-C3N4;

[0070] 2) dispersing the g-C3N4 (2 g) and NH4VO3 (1.0 g) obtained in step 1) in 50 mL of ultrapure water, and stirring in a water bath at 75° C. until the water is completely evaporated, to obtain a mixed material;

[0071] 3) The mixture obtained in step 2) is encapsulated in a crucible and wrapped tightly with tin foil, and calcined at 500°C for 2h in an air atmosphere with a heating rate set at 2.5°C / min. After the crucible is naturally cooled to room temperature, the collected solid is ground evenly and marked as V-CN-3.

[0072] Example 4

[0073] This embodiment provides a method for preparing a V2O5 / g-C3N4 composite material, and the specific steps are as follows:

[0074] 1) 5 g of melamine was placed in a covered crucible, and then placed in a muffle furnace, and calcined at 550 ° C for 4 h in an air atmosphere, with a heating rate of 5 ° C / min. After the crucible was naturally cooled to room temperature, the collected solid was ground into powder, which was marked as g-C3N4;

[0075] 2) dispersing the g-C3N4 (2 g) and NH4VO3 (1.4 g) obtained in step 1) in 50 mL of ultrapure water, and stirring in a water bath at 75° C. until the water is completely evaporated to obtain a mixed material;

[0076] 3) The mixture obtained in step 2) is encapsulated in a crucible and wrapped tightly with tin foil, and calcined at 500°C for 2h in an air atmosphere with a heating rate set at 2.5°C / min. After the crucible is naturally cooled to room temperature, the collected solid is ground evenly and marked as V-CN-4.

[0077] Comparative Example 1

[0078] This comparative example provides a method for preparing a g-C3N4 material, and the specific steps are as follows:

[0079] 5 g of melamine was put into a covered crucible, and then placed in a muffle furnace and calcined at 550 °C for 4 h in an air atmosphere. The heating rate was set to 5 °C / min. After the crucible was naturally cooled to room temperature, the collected solid was ground into powder and marked as g-C3N4.

[0080] Comparative Example 2

[0081] This comparative example provides a method for preparing a V2O5 material, and the specific steps are as follows:

[0082] 1) Disperse NH4VO3 (1.0 g) in 50 mL ultrapure water and stir in a water bath at 75 °C until the water is completely evaporated;

[0083] 2) The material obtained after evaporation in step 1) is encapsulated in a crucible and wrapped tightly with tin foil, and calcined at 500°C for 2h in an air atmosphere with a heating rate set at 2.5°C / min. After the crucible is naturally cooled to room temperature, the collected solid is ground evenly and marked as V2O5.

[0084] Test Example 1

[0085] The phase analysis of the V2O5 / g-C3N4 composite materials prepared in Examples 1-4 and the g-C3N4 and V2O5 prepared in Comparative Examples 1-2 was performed by X-ray diffraction (XRD). The XRD characterization results are as follows: Figure 1 As shown. From the XRD characterization results, it can be seen that V-CN (representing V-CN-1, V-CN-2, V-CN-3, V-CN-4) can observe characteristic peaks similar to g-C3N4 at 12.9° and 27.5°, corresponding to the (100) and (002) crystal planes of g-C3N4, respectively, which are caused by the in-plane repeating units and conjugated aromatic structures of the continuous heptazine framework. This shows that the introduction of V2O5 does not destroy the crystal structure of g-C3N4. However, with the increase of NH4VO3 dosage, the signal intensity of V-CN at (100) and (002) weakened to varying degrees, indicating that the crystallinity of g-C3N4 after secondary calcination gradually decreases with the introduction of V2O5, and the layers show short-range ordered stacking. In the XRD characterization results of V-CN, the reason why the diffraction peak intensity of V2O5 is weak may be due to the masking of the diffraction peak of g-C3N4. As the V2O5 doping amount increases, the g-C3N4 diffraction peak is gradually covered by V2O5, causing the intensity of the g-C3N4 diffraction peak to gradually weaken.

[0086] Test Example 2

[0087] The elemental composition and elemental valence of V-CN-3 prepared in Example 3 were further determined by X-ray photoelectron spectroscopy (XPS). The XPS characterization results are as follows: Figure 2As shown, C, N and O are common elements of g-C3N4 and V-CN-3, and with the successful introduction of V2O5, the XPS spectrum of V-CN-3 also showed a signal peak representing V 2p.

[0088] Test Example 3

[0089] The molecular structures of V-CN prepared in Examples 1-4, g-C3N4 prepared in Comparative Example 1, and V2O5 prepared in Comparative Example 2 were analyzed by Fourier transform infrared spectroscopy (FT-IR). Figure 3 and Figure 4 As shown in Figure 2, g-C3N4 and V-CN have similar FT-IR spectra. -1 The absorption peak at 1200-1650cm corresponds to the typical breathing vibration of tri-s-triazine unit. -1 The strong bands in the range of 3000-3500cm are attributed to the stretching modes of aromatic CN and C=N heterocycles. -1 The broad peak in the region is related to the amino groups in the structural defect sites. -1 A clear V2O5 band can also be observed nearby ( Figure 3 The part shown in the dotted box in the middle) did not damage the structure of g-C3N4.

[0090] Test Example 4

[0091] The V-CN-3 prepared in Example 3, the g-C3N4 prepared in Comparative Example 1, and the V2O5 prepared in Comparative Example 2 were studied by scanning electron microscopy (SEM). Figure 5-Figure 10 As shown ( Figure 5 and Figure 6 Corresponding to g-C3N4, Figure 7 and Figure 8 Corresponding to V-CN-3, Fig. 9 and Fig.10 Corresponding to V2O5), V-CN-3 presents a more obvious flaky structure compared to g-C3N4. V2O5 prepared in the same way also presents an obvious flaky structure, indicating that this may be because NH4VO3 attached to the surface of g-C3N4 releases gas during calcination, which causes gas stripping of g-C3N4. This structure is conducive to the exposure of active sites on the material.

[0092] Test Example 5

[0093] The catalytic performance of V-CN prepared in Examples 1-4, g-C3N4 prepared in Comparative Example 1, and V2O5 prepared in Comparative Example 2 was investigated by chloramphenicol degradation experiments, with g-C3N4, V-CN, V-CN and PMS compound, V2O5, and PMS as the investigation objects, respectively. The specific experimental operation method is as follows:

[0094] The following experimental operations were all carried out in a light-shielded reaction vessel with magnetic stirring.

[0095] Adsorption experiment: 30 mL of chloramphenicol solution (initial concentration C0 is 10 mg / L) and 9 mg of the prepared composite material were placed in a quartz reaction tube and stirred in the dark at a constant temperature (25°C) for 40 min. Samples were collected at specific time intervals (10 min). The measured concentration of the chloramphenicol solution was C. The test results are as follows: Fig.11 As shown. Fig.11 It can be seen that g-C3N4, V2O5 and V-CN have no obvious adsorption effect on chloramphenicol.

[0096] Formal degradation experiment: 30 mL of chloramphenicol solution (concentration of 10 mg / L) and 9 mg of the prepared composite material were placed in a quartz reaction tube and stirred in the dark at a constant temperature (25°C) for 40 min until the reaction system reached adsorption-desorption equilibrium (the concentration in the chloramphenicol solution was C0 at this time); then 1 mM (based on the volume of the chloramphenicol solution) of PMS was added to trigger the catalytic reaction, samples were collected at specific time intervals, and the sample solution was filtered through a 0.22 μm polyethersulfone filter membrane, a certain amount of filtrate was taken and immediately mixed with an equal volume of methanol and collected in a liquid phase injection bottle, and the chloramphenicol concentration (C) was determined using a high performance liquid chromatography (HPLC, waters e2695) equipped with a UV-visible detector and an Agilent C-18 chromatographic column (4.6 mm x 250 mm, 5 μm), wherein the mobile phase included 60% methanol and 40% 0.1 vol% formic acid aqueous solution, the flow rate was 1 ml / min, and the detection wavelength was 278 nm.

[0097] After testing, it was found that, under dark conditions, the use of PMS alone or g-C3N4 combined with PMS, or V2O5 combined with PMS system, could not effectively remove CAP (e.g. Fig.12 and Fig.13As shown, the time of adding PMS is taken as 0 min). In contrast, although g-C3N4 and V2O5 did not effectively activate PMS, V-CN successfully promoted the catalytic process and achieved the degradation of CAP. Remarkably, within only 5 min, the CAP removal rates of V-CN-1, V-CN-2, V-CN-3 and V-CN-4 reached 46.0%, 79.8%, 100.0% and 100.0%, respectively. This indicates that the heterogeneous structure between g-C3N4 and V2O5 plays a key role in the activation of PMS. According to Fig.13 As shown in Figure 2, the reaction constant (K) for V2O5 activation of PMS under light-free conditions is obs ) is almost 0, but in V-CN, with the increase of V2O5 content, the catalytic activity of V-CN initially increases and then stabilizes, and V-CN-3 is determined to be the best catalyst. Fig.14 As shown, the apparent first-order degradation kinetic rate constant of CAP by the V-CN-3 / PMS system is 1.13 min-1, which exceeds other reported catalytic systems and sets a new record.

[0098] Test Example 6

[0099] XPS analysis was performed on V-CN-3 before and after the activation of PMS (experimental operation was the same as in Test Example 5) to explore the role of vanadium (V) in the V-CN / PMS system. Fig.15 As shown, in the unused V-CN-3, the peaks at 517.0 eV and 524.0 eV confirm that vanadium exists in the form of V (V) before the reaction (the peaks at 517.0 eV and 524.0 eV in V-CN-3 are respectively attributed to the V 2p in V2O5 3 / 2 and V 2p 1 / 2 , verifying the successful construction of the V-CN heterojunction). After activating PMS with V-CN-3, characteristic peaks corresponding to V(IV) and V(III) appeared, indicating that V(V) was reduced to V(IV) / V(III) (Equation (1)). Due to the oxidizing property of PMS, V(IV) / V(III) was subsequently oxidized back to V(V) and SO4 was generated. ·- (Equation (2)). In addition, the binding energy of V(V) shifted before and after the reaction (517.2 eV and 523.7 eV), which was attributed to the built-in electric field (BIEF) between g-C3N4 and V2O5, which promoted the transfer of electrons from g-C3N4 to V2O5 (Equation (3)). Therefore, the BIEF in V-CN promoted the rapid cyclic conversion of V(III) / V(V) / V(IV) and accelerated the activation of PMS. In addition, SO5 ·– and SO4 ·– The reaction produces OH and O2 ·– and1 O2 (Equations (4) and (5)). Finally, the V-CN / PMS system is activated by free radicals (SO4 ·– , OH and O2 ·– ) and non-free radicals ( 1 O2) to achieve efficient degradation of CAP (Equation (6)).

[0100] V(V)+HSO5 - →V(Ⅳ) / V(Ⅲ)+SO5 ·- +H + (1);

[0101] V(Ⅳ) / V(Ⅲ)+HSO5 - →V(V) / V(IV)+SO4 ·- +OH - (2);

[0102] V(V) / V(IV)+e - (g-C3N4)→V(IV) / V(III) (3);

[0103] SO4 ·- +OH - → · OH+SO4 2- (4);

[0104] 2SO5 ·- +2H2O+e - (g-C3N4)→2SO4 2- + 1 O2+O2 ·- +4H + (5);

[0105] CAP+SO4 ·- / · OH / O2 ·- / 1 O2→H2O+CO2 (6).

[0106] Test Example 7

[0107] V-CN-3 was used to activate PMS to degrade CAP. The dosage of V-CN-3 was set to 0.1 g / L, 0.2 g / L, 0.3 g / L, 0.5 g / L and 1.0 g / L (based on the volume of chloramphenicol solution, the initial concentrations of V-CN-3 were 0.1 g / L, 0.2 g / L, 0.3 g / L, 0.5 g / L and 1.0 g / L, respectively). The effect of different V-CN-3 dosages on the degradation of CAP by the V-CN-3 / PMS system was explored. The detection operation steps were the same as those in Test Example 5. The test results are shown in Figure 5. Fig.16When V-CN activated PMS to degrade CAP, the dosage of V-CN was 0.1-1g based on 1L of chloramphenicol solution with an initial concentration of 10mg / L; considering the economy and degradation effect, the optimal dosage was 0.3g / L.

[0108] Test Case 8

[0109] V-CN-3 was used to activate PMS to degrade CAP. The PMS concentrations were set to 0.25mM, 0.50mM, 1.00mM, 1.50mM and 2.00mM (based on the volume of 30mL chloramphenicol solution, the initial PMS concentrations were 0.25mM, 0.50mM, 1.00mM, 1.50mM and 2.00mM, respectively). The effect of different PMS concentrations on the degradation of CAP by the V-CN-3 / PMS system was explored. The detection operation steps were the same as those in Test Example 5. The test results are shown in Figure 5. Fig.17 When V-CN activates PMS to degrade CAP, the concentration of PMS is 0.25-2mM based on the volume of 1L of chloramphenicol solution with an initial concentration of 10mg / L; considering the economy and degradation effect, the optimal dosage is 1.00mM.

[0110] Test Example 9

[0111] V-CN-3 was used to activate PMS to degrade CAP. The initial concentrations of CAP were set to 10 mg / L, 8 mg / L, 6 mg / L, 4 mg / L, 2 mg / L and 1.00 mg / L (based on the volume of chloramphenicol solution, the initial concentrations of CAP were 10 mg / L, 8 mg / L, 6 mg / L, 4 mg / L, 2 mg / L and 1.00 mg / L, respectively). The effect of different CAP concentrations on the degradation of the V-CN-3 / PMS system was explored. The detection operation steps were the same as those in Test Example 5. The test results are shown in Fig.18 As shown, the V-CN-3 / PMS system has a good degradation effect on CAP of different concentrations.

[0112] Test Example 10

[0113] V-CN-3 was used to activate PMS to degrade CAP. The pH values ​​were set to 2.03, 4.02, 5.87, 8.01 and 9.98 respectively to explore the effect of different pH values ​​on the degradation of CAP by the V-CN-3 / PMS system. The detection operation steps were the same as those in Test Example 5. The test results are shown in the figure. Fig.19 As shown, the V-CN-3 / PMS system has a good degradation effect on CAP in a wide pH range (2-10).

[0114] Test Example 11

[0115] Different ions (Cl - 、NO3- 、SO4 2- 、H2PO4 - ) and humic acid (HA) were used to test the interference of V-CN-3 / PMS system, and a control group without ion and HA interference was set up. The operation steps were the same as those in Test Example 5. The test results are shown in Fig. 20 As shown, the V-CN-3 / PMS system has different ions (Cl - 、NO3 - 、SO4 2- 、H2PO4 - ) and humic acid (HA) can completely degrade CAP within 10 min, indicating that the V-CN-3 / PMS system has strong resistance to different ions and HA.

[0116] Test Example 12

[0117] Ultrapure water, tap water, river water and other water matrices were used to conduct interference tests on the V-CN-3 / PMS system to test the anti-interference ability of the V-CN-3 / PMS system to real water matrices (tap water and river water). The operation steps were the same as those in Test Example 5. The test results are shown in Figure 2. Fig.21 As shown, the V-CN-3 / PMS system can completely degrade CAP within 10 min under ultrapure water, tap water and river water conditions, indicating that the V-CN-3 / PMS system has good applicability to different water bodies.

[0118] Test Example 13

[0119] V-CN-3 was recovered by filtration after each use and washed several times with sufficient alcohol and deionized water. The operation steps were the same as those in Test Example 5 to carry out a cycle test to test its chemical stability. The test results are shown in the figure. Fig. 22 As shown in the figure, after 5 cycles of experiments, the V-CN-3 / PMS system can still achieve efficient removal of CAP, indicating that the V-CN-3 / PMS system has good stability.

[0120] Test Case 14

[0121] V-CN-3 was used to activate PMS, and bisphenol S (BPS), chloramphenicol (CAP), atrazine (ATZ), bisphenol F (BPF), sulfamethoxazole (SMX), parachlorophenol (4-CP), caffeine (CAF), and bisphenol A (BPA) were degraded respectively to test the degradation effect of V-CN-3 / PMS system on different pollutants. The operation steps were the same as those in Test Example 5. Among them, the catalytic performance evaluation of V-CN / PMS system on different pollutants, except for the different types of pollutants, the other operations and conditions were consistent with the chloramphenicol degradation experiment. The test results are as follows Fig.23As shown in the figure, under lightless conditions, the V-CN-3 / PMS system can achieve good degradation effects on different pollutants and has broad application prospects.

[0122] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A composite material of activated persulfate, characterized in that: The composite material includes V2O5 and g-C3N4, and the composite material activates persulfate without additional energy input.

2. A method for preparing the composite material of activated persulfate according to claim 1, characterized in that: include: Obtain g-C3N4; mix g-C3N4 and NH4VO3 to obtain a mixture; and calcine the mixture.

3. The preparation method according to claim 2, characterized in that: The mass ratio of g-C3N4 to NH4VO3 is 2:(0.2-1.4); And / or, the calcination temperature is 400-600°C, preferably 500°C; And / or, the calcination treatment time is 1-3 hours, preferably 2 hours; And / or, the heating rate of the calcination treatment is 1-5°C / min, preferably 2.5°C / min; And / or, the specific process of the mixing treatment includes: dispersing g-C3N4 and NH4VO3 in a solvent to obtain a dispersion, and stirring the dispersion in a water bath until the solvent is completely evaporated; And / or, the calcination treatment is followed by natural cooling and grinding.

4. The preparation method according to claim 3, characterized in that: The solvent is water; And / or, based on the mass of g-C3N4 being 2g, the amount of the solvent used is 40-60mL, preferably 50mL; And / or, the temperature of the water bath is 65-85°C, preferably 75°C.

5. The preparation method according to any one of claims 2 to 4, characterized in that: The method for obtaining the g-C3N4 comprises: sintering melamine to obtain the g-C3N4.

6. The preparation method according to claim 5, characterized in that: The sintering temperature is 500-600°C, preferably 550°C; And / or, the sintering treatment time is 3-5 hours, preferably 4 hours; And / or, the heating rate of the sintering treatment is 4-6°C / min, preferably 5°C / min; And / or, the sintering process is followed by natural cooling and grinding.

7. Use of the composite material of activated persulfate according to claim 1 or the composite material of activated persulfate prepared by the preparation method of the composite material of activated persulfate according to any one of claims 2 to 6 in activating persulfate without additional energy input.

8. The use according to claim 7, characterized in that: The composite material degrades pollutants in water by activating persulfate.

9. The use according to claim 8, characterized in that: The persulfate is peroxymonosulfate and / or peroxydisulfate, preferably peroxymonosulfate; And / or, the pollutant is an organic pollutant.

10. The use according to claim 9, characterized in that: The organic pollutants include bisphenol S, chloramphenicol, atrazine, bisphenol F, sulfamethoxazole, p-chlorophenol, caffeine or bisphenol A.